2021
DOI: 10.3390/toxins13120902
|View full text |Cite
|
Sign up to set email alerts
|

Zearalenone Exposure Triggered Cecal Physical Barrier Injury through the TGF-β1/Smads Signaling Pathway in Weaned Piglets

Abstract: This study aims to investigate the effects of exposure to different dosages of zearalenone (ZEA) on cecal physical barrier functions and its mechanisms based on the TGF-β1/Smads signaling pathway in weaned piglets. Thirty-two weaned piglets were allotted to four groups and fed a basal diet supplemented with ZEA at 0, 0.15, 1.5, and 3.0 mg/kg, respectively. The results showed that 1.5 and 3.0 mg/kg ZEA damaged cecum morphology and microvilli, and changed distribution and shape of M cells. Moreover, 1.5 and 3.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Primer sequences used for real-time PCR in this study are shown in Supplementary Table 2 . The detailed procedure of the relative mRNA expression determination was described in Zhang P. et al (2021) . The β-actin gene was amplified in parallel as the internal control for gene normalization and quantification.…”
Section: Methodsmentioning
confidence: 99%
“…Primer sequences used for real-time PCR in this study are shown in Supplementary Table 2 . The detailed procedure of the relative mRNA expression determination was described in Zhang P. et al (2021) . The β-actin gene was amplified in parallel as the internal control for gene normalization and quantification.…”
Section: Methodsmentioning
confidence: 99%
“…The mucosa mRNA expression levels of tight junction proteins [(ZO-1, occludin (OCLN), claudin 2 (CLDN2), and claudin 3 (CLDN3)], nutrient transporters [(glucose transporter type 2 (GLUT2), Na+/glucose cotransporter (SGLT1), y+L amino acid transporter 1 (y+LAT1), cationic amino acid transporter 1 (CAT1), and fatty acid binding protein-1 (FABP1)], and inflammatory pathway genes [(Toll-like receptor 4 (TLR4), myeloid differentiation primary response 88 (MyD88), and nuclear factor-kappa B (NF-κB)] in intestinal samples were determined using a CFX-96 real-time PCR detection system (Bio-Rad, Hercules, CA, USA). The primer sequences used for real-time PCR and detailed procedure of the relative mRNA expression determination in this study refer to previous studies [ 17 , 19 ]. The β-actin gene was amplified in parallel as the internal control for gene normalization and quantification.…”
Section: Methodsmentioning
confidence: 99%
“…The uterus tissue was dehydrated successively in ethanol (60%, 70%, 80%, 90%, 95%, and 100%) and xylene solutions for 1.5 h, after fixation in 4% paraformaldehyde for 48 h. Subsequently, it was embedded in the paraffin wax, and cut to a 4-μm section that was mounted on a poly-L-lysine-coated glass slide using Leica RM 2235 microtome (Leica, Wetzlar, Germany), according to the methods of Zhang et al [ 78 ]. The sections of uterus were stained with hematoxylin and eosin, and sealed with neutral resin.…”
Section: Methodsmentioning
confidence: 99%